Psychological capital, job insecurity, and organizational commitment during the Covid-19 pandemic - Eva Fachria; Riani Rachmawati (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The COVID-19 pandemic does affect not only human life but also has a massive effect on economics and business welfare. In Indonesia, food and beverage service are one of the most affected business sectors at the early stage of COVID-19 transmission. In this sector, employees experience severe shocks due to the unstable existing policies causing psychological anxiety. Moreover, most companies implemented new policies such as reduced working hours, salary deductions, and temporary layoffs. Employee organizational commitment is one of the most valuable aspects of maintaining a company's sustainability in the VUCA situation. In this study, we conducted a quantitative analysis of 292 respondents using the Structural Equation Model to know the effect of Psychological Capital and Job Insecurity on Organizational Commitment by using Work Engagement as a mediating variable. The results state that psychological capital affects employee organizational commitment positively. In contrast, job insecurity has a negative impact on organizational commitment. The indirect effect of work engagement has a significant role in mediating the relationship between psychological capital and organizational commitment, but not for job insecurity. This research is expected to provide new insight for the management or business owners, especially in the food and beverage service sector, about which aspects are essential to maintain workers during the shock of the COVID-19 pandemic so that both workers and organizations can survive in conditions full of uncertainty.